2017
DOI: 10.7744/kjoas.20170001
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of herbicide resistance in weeds

Abstract: In major field crops, synthetic herbicides have been used to control weeds worldwide. Globally, herbicide resistance in weeds should be minimized because it is a major limiting factor for food security. Cross resistance can occur with herbicides within the same or in different herbicide families and with the same or different sites of action. Multiple resistance refers to evolved mechanisms of resistance to more than one herbicide (e.g., resistance to both ALS-inhibitors and ACCase-inhibitors) and this resista… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…According to HRAC (2015) Herbicide resistance is defined as " naturally occurring inheritability of some weed biotype within given weed population to survive a herbicide treatment that should under normal use condition, effectively control that weed population" (Aung et al, 2017). Resistance can be classified into two types on the basis of the mechanism of action of herbicides: Multiple Resistance: When the weed is resistant to two or more herbicides having different mechanism of action are said to be multiple resistant and the phenomenon is known as multiple resistance.…”
Section: Types Of Herbicide Resistancementioning
confidence: 99%
See 1 more Smart Citation
“…According to HRAC (2015) Herbicide resistance is defined as " naturally occurring inheritability of some weed biotype within given weed population to survive a herbicide treatment that should under normal use condition, effectively control that weed population" (Aung et al, 2017). Resistance can be classified into two types on the basis of the mechanism of action of herbicides: Multiple Resistance: When the weed is resistant to two or more herbicides having different mechanism of action are said to be multiple resistant and the phenomenon is known as multiple resistance.…”
Section: Types Of Herbicide Resistancementioning
confidence: 99%
“…From the above figure it can be clarly deduced that wheat fields reported highest hebicide resistance cases this is mainly due to pooror faulty spray technology and lackof new active ingredients and And the phase IV includes the degradation of these transported molecules (Bo et al 2017, Aung et al, 2017and Im et al, 2016. This is the cause of the induction of the resistance, because the herbicide is not able to reach the target site and in turn is metabolized after its entry into the plant vascular system by various enzymes.…”
Section: History Of Herbicide Resistancementioning
confidence: 99%
“…An experimental study of herbicide resistance in various populations of A. myosuroides has shown that the use of CH mixtures can contribute to the development of a multiple resistance mechanism in weeds [ 78 ]. Indeed, the number of weed populations insensitive to CHs with various MOAs (from 2 to 8 and more) is steadily growing [ 79 , 80 ]; in the future, both more accurate selection of active ingredients and more active use of agrotechnical and biological methods of weed control will be required [ 81 ].…”
Section: Current Trends In Herbicide Developmentmentioning
confidence: 99%
“…As plantas daninhas podem apresentar resistência em local-alvo e não-alvo. No local-alvo, a resistência pode ocorrer por mudanças bioquímica no local de ação do herbicida, enquanto que o nãoalvo ocorre através de mecanismos que reduzem o número de moléculas de herbicidas que atingem determinado local-alvo (Bo et al, 2017). Desta forma, o conhecimento das plantas daninhas e das moléculas disponíveis no mercado é fundamental para a realização de um cronograma de manejo, juntamente com outras medidas de controle.…”
Section: Uso De Herbicidas Na Cultura Da Sojaunclassified